Linguistic Inequality in Urban Jember: The Dominance of Javanese and the Marginalization of Madurese - Christianto, Daniel Ganda; Firlana, Ahmad; Islamy, Zenith Garda (CV. Era Digital Nusantara, 2025)
This study investigates the dominance of the Javanese language in urban Jember, East Java, and its implications for social dynamics and cultural identity. Despite the presence of significant Madurese-speaking communities, Javanese has emerged as the dominant language in public and social interactions, reflecting underlying societal hierarchies. Using Paulo Freire’s theory of oppression, this research explores how linguistic hegemony marginalizes minority languages, pressuring non-Javanese speakers to conform for social acceptance. Employing a quantitative methodology, data were gathered through structured surveys of Jember residents. The results of the study clearly show how language power and social class are connected. 72.7% of people regularly use Javanese when they talk to each other every day, and 86.4% of them say that speaking Javanese helps them to make better connections with other people and is very important for their social life. However, this dominance imposes assimilation pressures, evidenced by 81.8% of participants feeling the need to adjust their language to fit majority norms. The study further examines Bourdieu’s concept of symbolic power, which explains how Javanese holds cultural and social significance, making it a tool for reinforcing linguistic hierarchies. These dynamics lead to the marginalization of Madurese speakers, aligning with Freire’s notion of internalized oppression, where minority groups adopt the norms of dominant cultures to avoid exclusion. By highlighting these patterns, the research underscores the need to address the inequities embedded in language use and advocates for measures to preserve linguistic diversity. This study contributes to understanding how language reflects broader cultural power structures and shape’s identity in multi-ethnic communities.